Perbandingan Hasil Belajar Titrasi Asam basa menggunakan Model Guided Discovery dan Inquiry Learning dengan Teknik Diskysi Buzz Group - Gusti Rahmi; Zonalia Fitriza (Universitas Negeri Padang, 2023)
The COVID-19 pandemic has affected the education system in Indonesia, especially in the implementation of learning. Due to a lack of time, learning using a scientific approach does not go well. One way to overcome time constraints is to use discussion techniques in learning. Therefore, research is needed that aims to compare student learning outcomes using the Guided Inquiry and Discovery Learning learning models using the Buzz Group discussion technique on acid-base titration material. The research population was all students of class XI, IPA MAN 1, Kota Bukittinggi, consisting of 4 classes. The sample is determined by the random sampling technique. Class XI IPA 1, the experimental class, uses the guided inquiry model, and class XI IPA 2, the experimental class, uses the guided discovery model with the buzz group discussion technique. Posttest data collection was done in the form of essay questions, with a total of 65 questions. The results showed that there were differences in the average scores of the two experimental classes. Based on the results of hypothesis testing, it was concluded that learning using the guided inquiry and guided discovery models with the buzz group discussion technique differed significantly.